Feasibility of energy dispersive X-ray fluorescence for quantitative prediction of elemental profile in untreated bovine colostrum - D. Martini; M. De Marchi; A. Goi; M. Pozza; G. Niero (Journal of Dairy Science)
ABSTRACT: Colostrum is the first secretion produced by the mammary gland after calving, providing essential macronutrients and micronutrients to newborns. Monitoring elemental concentrations in bovine colostrum (BC) is crucial, as it serves for the physiological development and health of the neonates. Current gold-standard methods to determine elemental composition of BC are inductively coupled plasma optical-emission spectrometry or inductively coupled plasma MS. These techniques, however, are time-consuming, expensive, labor-intensive, and destructive, and they require sample preparation such as chemical matrix decomposition. In this view, energy dispersive X-ray fluorescence (ED-XRF) could represent a handy alternative. This study evaluated the effectiveness of ED-XRF for the prediction of Na, Mg, P, S, K, Ca, and Zn in BC measured through inductively coupled plasma optical-emission spectrometry as reference method. The performances of ED-XRF in predicting BC elemental composition were assessed on the entire dataset (comprising 160 samples of individual BC), on a training set (comprising 70% of the samples), and on a testing set (comprising 30% of the samples). The models demonstrated satisfactory goodness of fit for S (coefficient of determination in external validation, R2TE = 0.77) and Zn (R2TE = 0.74), indicating their suitability for rough screening of such elements, while showing lower association for Na, Mg, P, K, and Ca. Results of the present study could support the development of rapid screening approaches to assess S and Zn levels in BC, contributing to more informed supplementation strategies of such minerals for calves, thereby preventing deficiencies and supporting neonatal development.